Effects of land versus water based fitness program in improving aerobic fitness, muscular strength and speed among young male beginner soccer players - Esayas Hailu; Sangeeta Rani; Mola Deyou (Turkish Journal of Kinesiology, 2016)
The primary purpose of this study was to evaluate the effects of land versus water based fitness program in improving aerobic fitness, muscular strength and speed among Young Male Beginner Soccer Players. Twenty-four young male beginner soccer players from Mugher district were selected as subjects. Their ages were 14-17years. The subjects were randomly assigned to land based performing exercise group (LEG, 12 male) and water based performing exercise group (WEG, 12 male). They participated in land based and water based exercises (both deep and shallow water) training for 3 months, 3 days per week for 50 minutes. The fitness variables selected for the study were aerobic fitness, muscular strength, and speed. After 12 weeks of training, the WEG improved better in soccer types of physical fitness qualities. In aerobic fitness the WEG increase by 21% (600 yard run/walk 22% and 12 min run/walk 20%) and the LEG increased by 13% (600 yard run/walk 18% and 12 min run/walk 8%). Speed increased more by WEG as compare to LEG group. In 40-yard performance WEG showed 12% incremental change, while the LEG improved by 11%. In addition, 9% increment was observed in WEG and 7% improvement by the LEG was recorded in 60-meter speed performance. Muscle strength was highly enhanced in the WEG. I n barbell squat test, the WEG and LEG have shown 46% and 29% changes, respectively. These results indicated that long-term water based performing exercises were better than the land based performing exercises in improving aerobic fitness, muscular strength and speed of beginner soccer players.